Dual roles of Anisakis pegreffii proteins in macrophage immune dynamics - Zeng, Min-hao; Alsobaie, Sarah; Wang, Xiao-xu; Li, Shan; Aldakheel, Fahad M.; Aboul-Soud, Mourad A. M.; Liu, Wei-bin (Frontiers in Immunology, 2025)
BackgroundAnisakis infections have become a significant public health concern primarily caused by consuming raw or undercooked seafood. This in is due to a shift in global eating habits, and seafood consumption is becoming increasingly popular.Materials and MethodsThis study explores how Anisakis pegreffii body proteins (ABP) and glycoproteins affect macrophage polarization. The parasites collected from East China Sea hairtail fish (Trichiurus lepturus), with glycoproteins isolated from ABP via ConA magnetic beads. RAW264.7 macrophages were treated with ABP, glycoproteins, and co-incubated with LPS or IL-4, then analyzed by qPCR for TNF-α and Arg-1. Transcriptomic profiling and bioinformatics analyses also helped identify differentially expressed genes and pathways.ResultsThis study showed that ABP with LPS greatly upregulated TNF-α, boosting inflammation. Conversely, glycoproteins suppressed TNF-α transcription and reduced IL-4-induced Arg-1 expression, displaying immunosuppression. Transcriptomics analysis found that ABP enriched TNF and hematopoietic pathways, with IL6 and IL1β as key pro-inflammatory genes. Glycoproteins activated cytokine-cytokine receptor interactions and hampered leukocyte migration by downregulating Ccl2 and H3c7. Notably, ABP and glycoproteins differentially regulated the JAK-STAT pathway.ConclusionThis study shows that A. pegreffii induces a dual-pronged immune response: ABP exacerbates inflammation, while glycoproteins suppress it. This highlights glycoproteins’ potential as therapeutic targets for modulating parasitic immunopathology and inflammatory diseases. The analysis of ABP and glycoprotein - induced immune responses provides key insights into Anisakiasis pathogenesis and may help develop new treatments.